Genetic Determination of Serum Levels of Diabetes-Associated Adipokines (The Review of Diabetic Studies, 2015)
Adipose tissue secretes an abundance of proteins. Some of these proteins are known as adipokines and adipose-derived hormones which have been linked with metabolic disorders, including type 2 diabetes, and even with cancer. Variance in serum adipokine concentration is often closely associated with an increase (obesity) or decrease (lipodystrophy) in fat tissue mass, and it is affected by age, gender, and localization of the adipose tissue. However, there may be genetic variants which, in consequence, influence the serum concentration of a certain adipokine, and thereby promote metabolic disturbances or, with regard to the “protective” allele, exert beneficial effects. This review focuses on the genetic determination of serum levels of the following adipokines: adiponectin, chemerin, leptin, progranulin, resistin, retinol binding protein 4, vaspin, adipsin, apelin, and omentin. The article reports on the latest findings from genome-wide association studies (GWAS) and candidate gene studies, showing variants located in/nearby the adipokine genes and other (non-receptor) genes. An extra chapter highlights adipokine-receptor variants. Epigenetic studies on adipokines are also addressed.